A DNA Based Biosensor Amplified With ZIF-8/Ionic Liquid Composite for Determination of Mitoxantrone Anticancer Drug: An Experimental/Docking Investigation - Alizadeh, Marzieh; Azar, Parviz Aberoomand; Mozaffari, Sayed Ahmad; Karimi-Maleh, Hassan; Tamaddon, Ali-Mohammad (Frontiers in Chemistry, 2020)
An ultrasensitive DNA electrochemical biosensor based on the carbon paste electrode (CPE) amplified with ZIF-8 and 1-butyl-3-methylimidazolium methanesulfonate (BMIMS) was fabricated in this research. The DNA/BMIMS/ZIF-8/CPE was used for the selective determination of a mitoxantrone anticancer drug in aqueous solution, resulting in a good catalytic effect and a powerful ability for determining mitoxantrone. Also, the interaction of the mitoxantrone anticancer drug with guanine bases of ds-DNA was used as a powerful strategy in the suggested biosensor, which was confirmed with docking investigation. Docking study of mitoxantrone into the ds-DNA sequence showed the intercalative binding mode of mitoxantrone into the nitrogenous-based pairs of ds-DNA. The effective factors such as ds-DNA concentration, temperature, buffer types, and incubation time were also optimized for the fabricated mitoxantrone biosensor. The results showed that, under optimum conditions (T = 25°C; incubation time=12 min; pH= 4.8 acetate buffer solution and [DNA] = 50 mg/L), the DNA/BMIMS/ZIF-8/CPE could be used in mitoxantrone assay in a concentration ranging from 8.0 nM to 110 μM with a detection limit of 3.0 nM. In addition, recovery data between 99.18 and 102.08% were obtained for the determination of mitoxantrone in the injection samples using DNA/ZIF-8/BMIMF/CPE as powerful biosensors.